EXPLORING HOW ZOO SERVICESCAPES IMPACT MEMORABLE TOURISM EXPERIENCE: A CRITICAL INCIDENT TECHNIQUE (CIT) APPROACH - Jasmine Zea Raziah Radha Rashid-Radha; Nurhazani Mohd Shariff; Azilah Kasim; Raslinda Mohd Ghazali; Ahmad Edwin Mohamed (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This conceptual paper aims to investigate the impact of servicescapes on visitors’ experience of Malaysian zoos in order to show that the zoo’s physical environment plays an important role in determining a memorable tourism experience (MTE). In order to investigate the extent to which zoo-related servicescapes create memorable tourism experiences, the critical incident technique (CIT) is being proposed. Semi-structured interviews are to be conducted to ask visitors which aspects of their visit to the zoo were the most memorable in terms of hedonism, refreshment, local culture, novelty, meaningfulness, involvement, and knowledge. This study is expected to extend the servicescape framework to include new dimensions within the context of zoos. In terms of managerial implications, this study could assist zoo operators in understanding how visitors evaluate their trip to the zoo. Findings from this research could therefore provide insight into how zoological facilities, services, and attractions could be better managed to increase visitor numbers.